Stress and coping experience in Nurse Residency Programs for new graduate nurses: A qualitative meta-synthesis - Han, Peng; Duan, Xia; Wang, Lingmin; Zhu, Xiaoping; Jiang, Jinxia (Frontiers in Public Health, 2022)
Objectives To determine the stress experience and coping styles of new nurses during Nurse Residency Programs (NRPs) by identifying, appraising, and synthesizing data from the qualitative studies. Design A systematic review and meta-synthesis of qualitative studies. Review methods Eleven databases were systematically searched for relevant publications in March 2022. All qualitative and mixed-method studies in English and Chinese that explored the stress and coping experience during NRPs of new graduate nurses were included. The qualitative meta-synthesis was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. Two independent reviewers selected the studies and assessed the quality of each study. Meta-synthesis was performed to integrate the results. Results A total of 13 studies revealed 13 sub-themes and three descriptive themes: multi-dimensional stressors, somatic and emotional responses, coping resources and coping methods. Conclusion New nurses faced a lot of physical and emotional stress during NRPs, which had a negative impact on their physical and mental health. NRPs are a critical period for the career growth of new nurses. Effective management strategies must be implemented to improve nurse capacity, meet their needs, improve self-efficacy, and build organizational support, as this can improve the quality of clinical nursing and keep the enthusiasm and stability of the nursing team.